(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
This study was conducted to assess the procedure of fish feed production, analysis of nutritive value of feeds and its effect on growth of fish in selected fish farms. Five fish feed mills and fifteen fish farmers were randomly selected from Mymensingh district. Fish feeds were used by fifteen farmers among every three farmers used the feed of each mill. These feed Mills collect their Saudi Bangla and ACME fish feed are more preferable to the farmer due to higher protein and lipid content resulting more fish production. In this experiment, Saudi-Bangla fish feed mill (3843 Kg/ha/yr), Sunny fish feed mill (3761 Kg/ha/yr), Shushama fish feed mill (3581 Kg/ha/yr), Al-momen fish feed mill (3669 Kg/ha/yr), ACME fish feed mill (3796 Kg/ha/yr) was produce fish. Capital cost, operating cost, depreciation cost, total cost, revenue income and net profit were calculated and evaluated during the experimental period. In this study, those feed mills production capacity was 45000 ton/yr Saudi-Bangla fish feed mill, 45000 ton/yr Sunny fish feed mill, 35000 ton/yr Shushomo fish feed mill, 35000 ton/yr Al-momen fish feed mill,15000 ton/yr ACME fish feed mill. The fish production mainly carps and pangus were highly occurs chronologically Saudi-Bangla, ACME fish feed, Sunny fish feed, Al-momen fish feed, Shushama fish feed mill, respectively. Among those the nutritive value of Saudi-Bangla fish feed was the best than other fish feed. Res. Agric., Livest. Fish.2(2): 353-362, August 2015